FORMATION OF RESEARCH COMPETENCIES IN STUDENTS BASED ON AN INTEGRATIVE APPROACH - Egamberganov I. Sh. (Web of Journals Publishing, 2023)
The article considers that the integrative approach is an effective technology for the formation of research competencies among students on the example of processing experimental data obtained as a result of a physical experiment (mathematical and statistical analysis). The formation of research competencies among students was assessed on the basis of reproductive, productive and creative criteria.
Keywords: physical experiment, mathematical-statistical analysis, research competence, reproductive level, productive level, creative level.